Anaesthetic management of a patient with multiple pterygium syndrome for elective caesarean section. (May 2017) - Daga, V.; Mendonca, C.; Choksey, F.; Elton, J.; Radhakrishna, S.
Highlights: Airway management can be challenging in a patient with multiple pterygium syndrome. Preoperative preparation is the key to success. It is important to plan for the failure of an awake intubation. A multidisciplinary approach is advised for successful anaesthetic management. Abstract: We report a case of a pregnant woman with multiple pterygium syndrome who presented for elective caesarean section. Neuraxial anaesthesia failed and the backup plan of awake intubation was extremely difficult.